Biodiesel fuel. Part I. Methods of obtaining - S. V. Mazanov; F. M. Gumerov; R. A. Usmanov; A. R. Gabitova; Z. I. Zaripov; S. D. Varfolomeev; V. B. Vol'eva; Yu. A. Shapovalov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. The presented work aims to analyze the realities and prospects for the use of working media in the production of biodiesel fuel, including the supercritical fluid state. METHODS. Methods for obtaining biodiesel fuel are considered, including the method of transesterification, as the most common, as well as methods of pyrolysis and the combined process of hydrolysis and esterification. RESULTS. Traditional (industrially used methods for producing biodiesel fuel), as well as methods involving supercritical fluid media at their core, are considered. Along with a description of the state of affairs on the issues under discussion in the world, the results of our own research carried out by the team of authors of this article are also presented. Attention is drawn to the prospects of ultrasonic emulsification of the reaction mixture and the use of heterogeneous catalysts in order to mitigate supercritical fluid conditions for the process of obtaining biodiesel fuel and save energy. The conditions for obtaining biodiesel fuel without free glycerol and converting it into a fuel component are also discussed. CONCLUSION. Transesterification carried out under supercritical fluid conditions provides significant advantages over the traditional process and, especially in terms of the possibility of using a variety of raw materials, including low-quality ones, facilitates the procedure for isolating the final product and, finally, makes it possible to switch from relatively small-scale implementations with batch reactors to high-performance plants with flow reactors.